Critical Factors for Constructing an Effective Supply Chain Network - Tansakul, Nitipon; Suanmali, Suthathip; Charoensiriwath, Chayakrit; Shirahada, Kunio (International Journal of Supply Chain Management, 2018)
Supply Chain Management (SCM) is a source of value creation for stakeholders. There are many influential factors for constructing a partnership in supply chain network. The factors demonstrate different contributions in each phase of supply chain. The purpose of this study is to establish a theoretical framework for constructing an effective supply chain network. A literature review of supply chain studies was employed to identify the influential factors in the process of supply chain development and establish the critical phases for creating effective supply chain network. The framework can be served as a guideline for both academic research and practical applications of SCM.